PKM Pelatihan Pengembangan Sistem Penerangan Jalan Bertenaga Surya dengan Aplikasi Internet of Things (IoT) - Ahmad Muhtadi; Moh.Rosan Taufel Alfarobi; Lukky Mahendra (Yayasan Literasi Altruis Khatulistiwa, 2025)
This community service project aims to design and implement a solar-powered street lighting system integrated with the Blynk application using Internet of Things (IoT) technology. The partner community faces challenges due to limited access to street lighting infrastructure, which affects social activities and residents' safety, especially at night. The designed system utilizes solar panels as the primary energy source, batteries for power storage, a NodeMCU ESP8266 microcontroller as the control center, and the Blynk application that allows remote monitoring and control of the lights via smartphones. An LDR sensor is used to detect ambient light intensity so that the lights automatically turn on at night and off during the day. Additionally, users can access the system status and manually control the lights through the Blynk app. The implementation results show that the system operates effectively, is energy-efficient, and is easy for residents to use. Active community participation in the training and installation process also enhanced their understanding of renewable energy utilization and digital technology. This program makes a tangible contribution to improving the community’s quality of life by providing sustainable and environmentally friendly lighting. Moreover, this innovation has the potential to be replicated in other areas with similar characteristics and challenges.